Probiotics’ Effectiveness in Antibiotic-Induced Diarrhea - Adnan, Afzal Ahmad, Ishfaq Ahmad, Qiam Ud Din, Abdul Hameed (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: In Lakki Marwat, KPK, Pakistan’s Category C hospital, probiotics were utilized to establish its efficiency in countering Antibiotic-Induced Diarrhea. Determine the following was the aim of the secondary Objectives: At the hospital, antibiotics have been found to be a common cause of diarrhea. Its prevalence is noticeable, sometimes sporadically. Probiotics’ effectiveness when addressing Diarrhea caused by antibiotics are under evaluation. Probiotic therapy’s safety and tolerability are both crucial factors to consider. Materials and Methods: During the timeframe of Jan 2021 to Jan 2022, a study was carried out in Cat-C hospital Lakki Marwat. At the registered medical centre, various patients were included as part of the research. These patients had earlier received antibiotics for their health conditions. To facilitate the treatment, they were all given probiotics in the form of capsules or liquid drops. The University Ethics Board provided approval, and the Helsinki Declaration was followed while conducting the study. Throughout the treatment period, the patients were constantly observed for any gastrointestinal symptoms such as abdominal pain, diarrhea, and nausea. Results: In the study, there were 100 patients who participated, the majority of whom reported experiencing gastrointestinal symptoms while taking antibiotics. Specifically, a whopping 97% of patients noted symptoms. The most common of which was diarrhea, with 78% reporting this issue. However, patients who did take probiotics had less diarrhea than those who did not receive these supplements (P 0.05). Based on these findings, it’s clear that probiotics are an effective solution for those who suffer from antibiotic-related discomforts. Keywords: Antibiotic-induced Diarrhea, probiotics, safety, tolerability, Lakki Marwat, Pakistan